(untitled) (GYMNASIUM, 2008)
The general record of the medals in European, World and Olympic competitions show the existence of a system and of a school of gymnastics that created a tradition and enjoyed of appreciation and recognition on a worldwide plan, launching in the sportive world names of exception, of which Marian Drăgulescu and Marius Urzică, became real legends. The many sided activities performed during an important number of years, in view to continuously improve the training program of the gymnasts had as a sequence the appearance of a well structured system of great efficiency, that may be considered as a self school, recognized and appreciated in the whole world. The Romanian artistic gymnastics is a sportive discipline that succeeded to bring fame to our country in the whole world, gaining a well deserved respect and much admiration.